Research on 5G mobile networks in Vietnam, design selection and testing of 5G Mobile Communications Jamming Device - Trieu, Le Hai; Duan, Nguyen Hong; Vinh , Truong Thanh; Loan, Bui Thi Bich; Son, Nguyen Dinh; Son, Vu Van (Journal of Science and Technology on Information security, 2024)
According to the research presented by the authors in [1], we propose research content, applying new technical technologies to research and design 5G mobile communications jamming devices. The goal of research and product design is to meet the basic requirements of technical indicators, operating features as well as specific requirements of the Public Security. In this article, the authors introduce some initial results of testing and evaluating 5G mobile communications jamming devices in frequency bands n28, n40, n41 (in which, n41 is divided into two frequency bands n41A and n41B) and n77. This not only has practical significance in scientific research and technology mastery, but also serves as a basis for the authors to continue developing products applying SDR technology to design and manufacture intelligently controlled, adaptive jamming devices in the future, meet work requirements of the Public Security, while diversifying the methods of operation for the Public Security force in practice